Financing nutrition in India: Cost implications of the nutrition policy landscape 2019-20 - Kapur, Avani; Shukla, Ritwik; Thakkar, Manan; Menon, Purnima (Centre for Policy Research, 2020)
India should have spent at least ₹38,571 crore in 2019-20, across Union government ministries and State government departments to fully finance a set of core direct nutrition interventions (DNIs), at scale. In this study, you will find information on nutrition costing. It carries forward critical studies that costed for nutrition interventions.